Representation of Feminism In The Film Samjin Company English Class (2020): A Semiotic Analysis - Esteria Ernawati Hutauruk; Mike Wijaya Saragih (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2023)
This paper aims to find the representation of feminism in the film Samjin Company English Class (2020). This film was written by Lee Jong-pil and set in 1995. This film tells the story of three girlfriends working for eight years in a large company in South Korea. Even though they have worked for a long time, the three of them are still treated differently. This film shows how female employees who only graduated from high school are able to prove their strengths by figuring out some cases of company waste leakage and corruption committed by company officials. They also fight for equal rights in their work. Their efforts, struggles, and courage are finally not in vain. The method used in this paper is a descriptive method. This research uses Roland Barthes’ semiotic theory to analyze the representation of feminism in the film. Signs and meanings are analyzed through some scenes and dialogues in the film showing the struggles of the three friends. The result of this research is the finding of 13 scenes that represent feminism which can be seen from the female characters’ struggle to grab their dreams.